2010
DOI: 10.1017/s1047951110000648
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil in the management of the failing Fontan circulation

Abstract: Sildenafil can be used safely and effectively in the treatment of patients with a failing Fontan circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 16 publications
0
38
0
2
Order By: Relevance
“…A prospective, randomized exercise study reported that sildenafil increases maximum O 2 consumption in Fontan patients at sea level. 365 Several case reports indicate beneficial effects of sildenafil in Fontan patients at low altitude, 410,587,588 but most of the patients underwent other interventions during the study period. A double-blind, placebo-controlled, crossover RCT of sildenafil for 6 weeks on exercise performance at sea level found small improvements in respiratory rate and minute ventilation at peak exercise.…”
Section: High Altitude and Chdmentioning
confidence: 99%
“…A prospective, randomized exercise study reported that sildenafil increases maximum O 2 consumption in Fontan patients at sea level. 365 Several case reports indicate beneficial effects of sildenafil in Fontan patients at low altitude, 410,587,588 but most of the patients underwent other interventions during the study period. A double-blind, placebo-controlled, crossover RCT of sildenafil for 6 weeks on exercise performance at sea level found small improvements in respiratory rate and minute ventilation at peak exercise.…”
Section: High Altitude and Chdmentioning
confidence: 99%
“…Experience with phosphodiesterase-5 inhibitors has shown clinical improvement in failing Fontan patients, 5 which, along with our finding of elevated PVRi in the PVE group, suggest a possible role for pulmonary vasodilators to optimize hemodynamics in failing Fontan patients before OHT. Our findings also support thorough as- sessment and aggressive embolization of APCs in failing Fontan patients before OHT to possibly limit intraoperative bleeding and subsequent graft failure after OHT.…”
mentioning
confidence: 52%
“…It is well established that endothelin receptor antagonists such as bosentan, sitaxentan, and ambrisentan improve the clinical symptoms and haemodynamic status of various types of pulmonary arterial hypertension [16][17][18][19]. Recently, the beneficial effects of pulmonary vasodilators administered to Fontan candidate patients or failing Fontan patients have also been reported [20][21][22][23][24]. For the Fontan candidate patients, low pulmonary vascular resistance is the most crucial factor in predicting the success of the Fontan operation; therefore, high pulmonary vascular resistance (N3 Wu m 2 ) is considered a contraindication to the Fontan surgery.…”
Section: Discussionmentioning
confidence: 99%